Efektywność wykorzystania klocków LEGO w terapii dzieci z ASD – perspektywa nauczycieli i terapeutów - Snadny, Krzysztof (Studia Edukacyjne, 2025)
The article aims to assess the effectiveness of using LEGO bricks as a therapeutic tool in working with children on the autism spectrum (ASD) from the perspective of practitioners. The article presents the results of a survey conducted among 50 teachers and therapists working with children with ASD. A diagnostic survey method (an online questionnaire) was employed to investigate the frequency of LEGO use, the perceived (social, emotional, educational) therapeutic benefits, and the barriers to implementing this form of therapy. The findings suggest a positive impact of LEGO therapy, as the respondents most frequently observed the development of creativity, fine motor skills, as well as increased motivation and concentration in children. Stress reduction and some improvement in social and communication skills were also reported. At the same time, the use of LEGO bricks is not widespread; only about one-third of the respondents reported employing them, primarily due to a lack of resources and training. In the discussion, the results are generalized to the broader context of the literature: LEGO therapy emerges as a promising approach supporting the social and emotional development of children with ASD, though its wider application requires increased awareness, institutional support, and integration with other evidence-based methods. The conclusions indicate that LEGO bricks may constitute an attractive and effective tool for the therapy and education of children with ASD, provided adequate conditions for implementation (materials, training) are ensured and their use is thoughtfully combined with other therapy forms. The article contributes a new analysis of original research data, indicating practical implications and recommendations for specialists.